A Resource-Based View (RBV) of Singapore as A Pre-Eminent Wealth Management Centre - Pena Mora, Yadir Adriana (2007)
Singapore is a world recognised financial and wealth management centre, and one of the best in the Asia-Pacific region. The fast growth of the world’s private wealth is boosting the wealth management sector, making this segment of the financial industry very attractive. Both big and small players are concentrating their efforts in this direction. Singapore has benefited from this growth. The question asked is “how and why is Singapore attracting the private wealth and institutions?” Especially when put in the context of Singapore competing against Hong Kong in the Asian region. The Resource-Based View (RBV) of strategy, argue that the success of a firm depend on internal resources. These resources may vary from human, financial, physical and technical resources, to name a few. The RBV is used here to examine the link between Singapore’s internal resources and its performances as the fastest-growing wealth management hub. Singapore Inc., as it has been referred to, has many resources that can give a competitive advantage to the island-state, however for this particular analysis, a positive reputation is selected as a resource that may provide the attributes (valuable, rare, imperfectly imitable and imperfectly substitutable), required by the RBV to give a sustainable competitive advantage to Singapore.